2021
DOI: 10.3389/feart.2021.781117
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Trench-Parallel Subduction of the Middle Ocean Ridge

Abstract: Trench-parallel subduction of mid-ocean ridges occurs frequently in plate motion history, such as along the western boundary of the Pacific plate in the early Cenozoic and along the eastern boundary of the Pacific plate at present. Such subduction may strongly alter the surface topography, volcanic activity and slab morphology in the mantle, whereas few studies have been conducted to investigate its evolutionary process. Here, we construct a 2-D viscoelastoplastic numerical model to study the modes and key par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…When a ridge approaches a convergent margin, the integrated effects of buoyancy and slab weakening at ridge axis (Beaussier et al., 2019; Gurnis et al., 2004; Qing et al., 2021) could result in the cessation of subduction and subsequent break‐off and detachment of the subducting slab (Burkett & Billen, 2009, 2010; Shen & Leng, 2021). Nevertheless, other studies suggested that ridge subduction may be uninterrupted and even the youngest parts of the oceanic slab could be drawn into the trench (Aragón et al., 2013; Scalabrino et al., 2009; Thorkelson et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When a ridge approaches a convergent margin, the integrated effects of buoyancy and slab weakening at ridge axis (Beaussier et al., 2019; Gurnis et al., 2004; Qing et al., 2021) could result in the cessation of subduction and subsequent break‐off and detachment of the subducting slab (Burkett & Billen, 2009, 2010; Shen & Leng, 2021). Nevertheless, other studies suggested that ridge subduction may be uninterrupted and even the youngest parts of the oceanic slab could be drawn into the trench (Aragón et al., 2013; Scalabrino et al., 2009; Thorkelson et al., 2011).…”
Section: Introductionmentioning
confidence: 99%